A New Size Reduction Method For Radial Line Slot Array (RLSA) Antennas - Purnamirza, Teddy; Muhammad Soleh, Muhammad Soleh; Asmarita, Asmarita; Mohd Ibrahim, Imran; Rahmi, Depriwana (Praise Worthy Prize, 2020)
A new size reduction method was introduced in this study for the radial line slot array (RLSA) antenna with the effects of the cutting used on antennas’ performance discussed to analyze the possibility of the method’s implementation. Moreover, the RLSA model and its cut version were designed, simulated, and fabricated to verify the method and its simulation, after which their performances were measured in terms of gain, S11, and bandwidth. The analysis of the simulation and results showed the method has the ability to minimize antenna size by up to four times while maintaining its gain which was observed to have decreased by only approximately 50%. The other good effect of the method is the wider bandwidth of the antenna which was estimated to be 0.2 GHz.